Solving the Assignment Problem Using Continuous-Time and Discrete-Time Improved Dual Networks - Hu, Xiaolin; Wang, Jun (IEEE transaction on neural networks and learning systems, 2012)
The assignment problem is an archetypal combinatorial optimization problem. In this brief, we present a continuous-time version and a discrete-time version of the improved dual neural network (IDNN) for solving the assignment problem. Compared with most assignment networks in the literature, the two versions of IDNNs are advantageous in circuit implementation due to their simple structures. Both of them are theoretically guaranteed to be globally convergent to a solution of the assignment problem if only the solution is unique.